Understanding Experiences of Youth with Long COVID: A Qualitative Approach - Chelsea Torres; Kensei Maeda; Madeline Johnson; Leonard A. Jason (MDPI AG, 2024)
There is limited information on the specific impacts of Long COVID in youth. Long COVID presents as persisting or new symptoms following initial COVID-19 infection. The aim of this study was to better understand how children and their families describe their experiences seeking diagnosis and support following the onset of symptoms of Long COVID. Six children and five caregivers located in the United States participated in this study. Study procedures included an online video interview with caregiver-child dyads. Interview transcriptions were then analyzed using a conventional approach to content analysis, with two independent coders generating themes. Eight themes emerged from this analysis including the severity of illness and symptomatology, difficulty surrounding the diagnostic process and not being believed, the impact on family and social connections, poor school functioning, positive coping, subsequent positive medical experiences, mental health, and knowledge of the medical field and healthcare experience. Themes revealed difficulty for youth and families in navigating the medical system and functioning in areas of daily life as well as areas of positive experiences related to coping and medical involvement. These findings also highlighted areas of needed improvement for the medical community and for research on Long COVID in youth.